(untitled) (Kairaranga, 2008)
The release of The New Zealand Curriculum causes us to rethink the aims of education. Dr Cavanagh offers an alternative set of aims to the vision outlined in the Ministry of Education document, which is based, at least in part, on socialisation into the corporate industrial world. Dr Cavanagh’s position is focused on putting relationships at the centre of who and what we are as schools. He believes if we create a culture of care in schools, students will be happy and flourish. As a result, the two major domains of schooling will be joined together - student behaviour and teacher pedagogy. This emphasis will help students and teachers to build their capacity to solve problems non-violently by learning how to build healthy relationships and heal broken relationships.